2009
DOI: 10.1177/1403494808100276
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes towards priority-setting and rationing in healthcare — an exploratory survey of Swedish medical students

Abstract: Future discussion about priority-setting in medical education should be contextualized within an explicit and open process. There is a need to adequately clarify the role of the cost-effectiveness principle in priority-setting. Medical students seem to acknowledge the need for rationing in healthcare to a greater extent when compared with previous results from Swedish primary care patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…The younger physicians recalled working with ethical questions during medical studies, but they did not concern dilemmas in relation to prioritisation and they had limited knowledge concerning the guidelines from the Swedish Parliamentary Priority Commission. Omar et al [12] who showed that knowledge about the priority principles is thoroughly disseminated among Swedish medical students although it's contextualisation within an open process is clearly lacking it is however important to remember that study took place among students in the same University where the Swedish Parliamentary Priority Commission is established and the result could perhaps not be generalised to other medical students.…”
Section: Discussionmentioning
confidence: 99%
“…The younger physicians recalled working with ethical questions during medical studies, but they did not concern dilemmas in relation to prioritisation and they had limited knowledge concerning the guidelines from the Swedish Parliamentary Priority Commission. Omar et al [12] who showed that knowledge about the priority principles is thoroughly disseminated among Swedish medical students although it's contextualisation within an open process is clearly lacking it is however important to remember that study took place among students in the same University where the Swedish Parliamentary Priority Commission is established and the result could perhaps not be generalised to other medical students.…”
Section: Discussionmentioning
confidence: 99%
“…e majority of medical students worldwide learn predominantly details of physiology, pathology and disease management. Although public health, global health and health policy are being introduced as part of the mandatory curriculum, the literature reveals that such programs exist only at a fraction of undergraduate medical institutions and/or are in their infancy and need substantive development [5][6][7][8][9][10][11], with fewer initiatives at programs in other health professionals [12,13]. Furthermore, healthcare is evolving towards an interprofessional model of healthcare delivery, a perspective that is not fully integrated in current e orts, but is compulsory in any meaningful e ort to shape equitable health policies.…”
mentioning
confidence: 99%